Increasing the efficiency of students’ learning process at a university through physical education - Sharonova A.V.; Mironova O.V.; Yarchikovskaya L.V.; Mikhailov B.A.; Vashchuk O.V.; Kiprushina I.I. (Theory and Practice of Physical Culture, 2024)
Objective of the study was to develop and implement the main ways to increase the efficiency of the learning process of students at a university using physical education. Methods and structure of the study. The experiment was conducted in the 2022/23 academic year. First-year students of the Russian State Hydrometeorological University (EG, n=12) and Saint Petersburg State University (CG, n=10) took part in the study. The authors analyzed the sanitary and hygienic conditions of training, professionally important qualities, as well as information about the physical activity of students. Research results. As a result of generalization and analysis of the data obtained, it was found that not only a properly organized educational process, but also a complex of health and hygiene measures, as well as sufficient physical activity of students, plays an important role in increasing the efficiency of the learning process of students at a university. Regular physical education classes in conditions of intense educational activity are an accessible and effective means of preventing mental and psychophysiological fatigue, which increases the effectiveness of learning. Results and conclusions. As a result of generalization and analysis of the data obtained, the dynamics of individual indicators of the hygienic conditions of student learning were established. Semester, weekly and daily changes in these indicators were obtained, however, only the daily dynamics of temperature and relative air humidity, as the most influential on the condition and performance of students, can be classified as natural. Regular physical education classes in conditions of intense educational activity are an accessible and effective means of preventing mental and psychophysiological fatigue, which increases the effectiveness of learning.